A molecular perspective on Late Quaternary climate and vegetation change in the Lake Tanganyika basin, East Africa - Tierney, J. E.; Russell, J. M.; Huang, Y. S. (Quaternary Science Reviews, 2010)
Characterizing the nature of past hydrological change and its interactions with vegetation is fundamental to acquiring a better understanding of continental tropical climate dynamics. Here, we outline major shifts in the climate and ecosystem of tropical East Africa for the past 60,000 years (60 ka) by examining molecular records of hydrology, vegetation, and temperature from a sediment sequence from Lake Tanganyika. We demonstrate, via comparison with pollen spectra, that stable carbon isotopes measured on higher plant leaf waxes (delta C-13(wax)) are a reliable proxy for vegetation change. In addition we argue that the D/H ratio of higher plant leaf waxes (delta D-wax) is a robust and independent indicator of past changes in aridity, and is not affected by regional vegetation change directly. Our paired, compound-specific isotope data show that shifts in vegetation lead major changes in hydrology in the Tanganyika basin at several major climate transitions during the past 60,000 years, suggesting that vegetation in the Tanganyika basin is not as sensitive to aridity as previous studies have suggested and that variations in carbon dioxide, temperature, and internal ecosystem dynamics are equally, if not more, important. We hypothesize that regional vegetation change may exert a positive feedback on regional hydrology, thus partially accounting for the abrupt threshold behavior evident in our paleohydrological data. Furthermore, we find that past changes in Tanganyika basin climate and ecology are closely linked to concentrations of atmospheric trace gases, highlighting the paramount influence of global climatic shifts upon regional tropical climate over glacial/interglacial timescales. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1850; 574XV Times Cited:0 Cited References Count:111Y